2000
DOI: 10.1046/j.1365-2141.2000.02145.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor and erythropoietin inhibit apoptosis of human erythroid progenitor cells through different signalling pathways

Abstract: Summary. Erythropoietin (EPO) and stem cell factor (SCF) are two important factors in human erythropoiesis. We have recently demonstrated that SCF and EPO synergistically activate mitogen-activated protein (MAP) kinase, thereby promoting growth of human erythroid colony-forming cells (ECFCs). In the present study, we have examined the intracellular mechanisms by which SCF and EPO maintain survival of these cells. In the absence of SCF and EPO, human ECFCs underwent rapid apoptosis. The process was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 47 publications
2
51
0
3
Order By: Relevance
“…Nonmegakaryocytic progenitors from ET and PV patients were just as sensitive as the MMM progenitors (median IC 50 20 nM, range 5-47 nM, P ÂŒ 0.17) (Figure 1). In contrast, higher median R115777 IC 50 concentrations were required for inhibition of nonmegakaryocytic progenitors from normal controls (median 46 nM, range 6-118 nM) (Figure 1), although this difference was not statistically In vitro antiproliferative activity of farnesyltransferase RA Mesa et al significant among any of the three groups because of the wide range in sensitivity within each group.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Nonmegakaryocytic progenitors from ET and PV patients were just as sensitive as the MMM progenitors (median IC 50 20 nM, range 5-47 nM, P ÂŒ 0.17) (Figure 1). In contrast, higher median R115777 IC 50 concentrations were required for inhibition of nonmegakaryocytic progenitors from normal controls (median 46 nM, range 6-118 nM) (Figure 1), although this difference was not statistically In vitro antiproliferative activity of farnesyltransferase RA Mesa et al significant among any of the three groups because of the wide range in sensitivity within each group.…”
Section: Resultsmentioning
confidence: 96%
“…41 It has been shown that both the PI-3 kinase pathway and the Mek pathway are involved with downstream signaling from a variety of critical hematopoietic growth factors, including erythropoietin and stem cell factor. 50,51 In addition, inhibition of the PI-3 kinase and Mek1 pathways has been shown to inhibit the growth of erythroid progenitors through potentially different mechanisms. 50,51 Since circulating progenitor cells in MMM constitute only a small fraction of the circulating mononuclear cells, it was not feasible to assess the effects of R115777 on these pathways using a biochemical approach.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on hematopoietic progenitors as well as in a study on neuronal cell cultures, an Epo-induced activation of the MEK/MAPK pathway has been demonstrated. 43,[51][52][53] To investigate the functional significance of this part of the Epoinduced signal transduction in vivo, we treated rats with a combination of Epo and PD 98059, a selective and cellpermeable inhibitor of the single upstream kinase MEK. 54 Under this combined treatment, RGC counts were only moderately decreased when compared to Epo monotherapy, indicating that phosphorylation of MAPKs has a smaller impact on Epo-induced RGC survival than activation of PI3-K/ Akt.…”
Section: Discussionmentioning
confidence: 99%
“…7D) in bone marrow following VEGFR-2 dimerization. Either of these kinases could account, at least in part, for the survival that we observed in response to VEGFR-2 dimerization, since induction of these signaling pathways by other hematopoietic cytokines, such as SCF and erythropoietin, has been implicated in hematopoietic cell survival (35)(36)(37).…”
Section: Vegfr-2 Activates the Pi 3-kinase And Erk Map Kinasementioning
confidence: 98%